1884 Compiled Laws of the Hawaiian Kingdom, at 539, An Act to License the Carrying of Fowling Pieces and Other Fire Arms - (:unkn) unknown (My University, 1884)
The general and indiscriminate use of fire-arms, which are frequently used for the destruction of useful, imported and migratory insectivorous birds and their progeny, is an injury to the agricultural and pastoral interests of this Kingdom, therefore, Be it Enacted by the King and Legislative Assembly of the Hawaiian Islands in the Legislature of the Kingdom assembled: § 1. That the Minister of the Interior may at any time license for a term of one year, any applicant for such license, to use and carry fire-arms for sporting purposes, in the District of Kona, Island of Oahu, on receiving for such license the sum of five dollars. § 2. Any person in said district who shall use or carry for sporting purposes, any gun, carbine, rifle, pistol, or other fire-arms, without having at first obtained a license as hereinbefore provided, shall, upon conviction therefor, before any police or district justice, be fined in a sum not to exceed fifty dollars for every such offense, and in default of payment of such sum, shall be imprisoned at hard labor, until such fine and costs are paid, according to law.
Keywords: HUNTING REGULATION